The natural stilbenoid pinosylvin and activated neutrophils: effects on oxidative burst, protein kinase C, apoptosis and efficiency in adjuvant arthritis - Jančinová Viera; Perečko Tomáš; Nosáľ Rado; Harmatha Juraj; šmidrkal Jan; Drábiková Katarína (Acta Pharmacologica Sinica, 2016)
Aim: To investigate the effects of the naturally occurring stilbenoid pinosylvin on neutrophil activity in vitro and in experimental arthritis, and to examine whether protein kinase C (PKC) activation served as an assumed target of pinosylvin action. Methods: Fresh human blood neutrophils were isolated. The oxidative burst of neutrophils was evaluated on the basis of enhanced chemiluminescence. Neutrophil viability was evaluated with flow cytometry, and PKC phosphorylation was assessed by Western blotting analysis. Adjuvant arthritis was induced in Lewis rats with heat-killed Mycobacterium butyricum, and the animals were administered with pinosylvin (30 mg/kg, po) daily for 21 d after arthritis induction. Results: In isolated human neutrophils, pinosylvin (10 and 100 μmol/L) significantly decreased the formation of oxidants, both extra- and intracellularly, and effectively inhibited PKC activation stimulated by phorbol myristate acetate (0.05 μmol/L). The inhibition was not due to neutrophil damage or increased apoptosis. In arthritic rats, the number of neutrophils in blood was dramatically increased, and whole blood chemiluminescence (spontaneous and PMA-stimulated) was markedly enhanced. Pinosylvin administration decreased the number of neutrophils (from 69 671±5588/μL to 51 293±3947/μL, P=0.0198) and significantly reduced the amount of reactive oxygen species in blood. Conclusion: Pinosylvin is an effective inhibitor of neutrophil activity, and is potentially useful as a complementary medicine in states associated with persistent inflammation.